Progress and challenges of personalized neoantigens in the clinical treatment of tumors - Hongyu Zhang; Xianchao Zhou; Dongliang Liu; Yufei Zhu; Qingyang Ma; Yuchao Zhang (Elsevier, 2020)
Tumors are a serious threat to human health, and tumor treatments have continued to evolve from chemotherapy to targeted therapy, immunotherapy, and individualized immunotherapy. Tumor cells have many mutations that cause the production of neoantigens, which are unique to tumor cells. Tumor neoantigen vaccines can effectively activate the body's immune system to kill tumor cells, making individualized immunotherapy based on tumor neoantigens a new direction for the development of personalized immunotherapy for tumors. This technique is unique in that it can kill cancer cells without damaging healthy tissues, it can target and attack tumors in any part of the body, it has minimal toxicity, and it is effective for almost all forms of cancer, allowing immune cells to "remember" cancer cells to prevent tumor recurrence. Tumor neoantigen vaccines are not only therapeutic but may also exert a preventive effect in high-risk groups. This therapy may also be applied to other diseases that can produce neoantigens, including infectious diseases, which increases the potential for broad application.